Anesthesia for fetal surgery. Issue 4 (17th February 2017) - Hoagland, Monica A.; Chatterjee, Debnath
Summary: Fetal therapy is an exciting and growing field of medicine. Advances in prenatal imaging and continued innovations in surgical and anesthetic techniques have resulted in a wide range of fetal interventions including minimally invasive, open mid‐gestation, and ex‐utero intrapartum treatment procedures. The potential for maternal morbidity is significant and must be carefully weighed against claimed benefits to the fetus. Appropriate patient selection is critical, and a multidisciplinary team‐based approach is strongly recommended. The anesthetic management should focus on maintaining uteroplacental circulation, achieving profound uterine relaxation, optimizing surgical conditions, monitoring fetal hemodynamics, and minimizing maternal and fetal risk.